71 Optimising patient active role in chronic disease management with a user-centered ehealth platform (CONCERTO+): a solution to overuse?. (4th December 2019) - Gagnon, Marie-Pierre; Ndiaye, Mame Awa; Larouche, Alain; Chabot, Guylaine; Chabot, Christian; Buyl, Ronald; Fortin, Jean-Paul; Giguère, Anik; LeBlanc, Annie; Légaré, France; Motulsky, Aude; Sicotte, Claude; et al.
Abstract : Objectives: Multimorbidity increases care needs and primary care use among people with chronic diseases. The Concerto Health Program (CHP) has been developed to optimise chronic disease management in primary care services. However, in its current version, the CHP primarily targets clinicians and does not aim to answer directly the needs of individual patients and their informal caregivers. This study aims to develop, implement and evaluate a user-centered, multifunctional and personalised eHealth platform (CONCERTO+) to promote a more active patient role in chronic disease management and decision-making. Method: This ongoing project uses a collaborative research approach and has 3 major phases: 1) the development of a multi-module eHealth platform combining scientific evidence and user-centered design; 2) a feasibility study of the CONCERTO+ solution through a pilot cluster randomised controlled trial where patients with multiple chronic diseases from a primary healthcare practice will receive CONCERTO+ during 6 months and be compared to patients from a control practice receiving usual care; and 3) an analysis of CONCERTO+ potential for scaling up. Results: The first phase of the project was the development of the user-centered solution. A first prototype was developed in Fall 2018 and tested with 10 patients and caregivers. Their comments led us to develop a second prototype that was tested with 10 patients and caregivers in Spring 2019. Following these 2 iterations, a final version of CONCERTO+ was developed and integrated to a large eHealth portal that enables information exchange and communication between health care providers and patients. The next phase, which consists of a pilot trial with diabetic patients followed in primary care practices, is ongoing. Conclusions: Digital health solutions such as patient portals have been found to improve self-management for chronic care conditions. By fostering a more active role of patients, it is hypothesised that a solution like CONCERTO+ could optimise the use of health care services and decrease emergency visits.